Hungarian Monitoring, 15 December 1988 . [Magyar rádiófigyelő], 1988. december 15 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - American-PLO dialog - Situation in Armenia - V. Biľak resigns - UN General Assembly session in Geneva comes to a close - Mikhail Moiseev the new chief of Soviet general staff - News of Armenian catastrophe received as cause for celebration in Azerbaijan - Latest news on the killers of Olof Palme Domestic Affairs: - Károly Grósz chairs Party Central Committee meeting - Genscher's visit to Budapest - Parliamentary Legal Committee in session on detailed modifications to the constitution, draft law on right to assemble and associate - Almost 2,000 people signed petition to demand recall of parliamentary representative Dr Miklós Vida; Alliance of Young Democrats (Fidesz) hold press conference on petition - Hungarian Democratic Forum (MDF) Kispest group held membership recruitment event yesterday - "After Arad, where next?", about Transylvanian refugees - Gabčíkovo-Nagymaros dam discussed at parliament ad hoc committee Külpolitika: - Amerikai-PFSZ párbeszéd - Örményországi helyzetkép - Lemondott V. Biľak - Véget ért az ENSZ genfi ülésszaka - Mihail Mojszejev az új szovjet vezérkari főnök - Azerbajdzsánban örömünnepként fogadták az Örményországi katasztrófa hírét - A Palme gyilkosság újabb hírei Belpolitika: - Grósz K. elnökletével ülésezik a párt Központi Bizottsága - Genscher budapesti látogatása - Ülésezik a Parlament Jogi Bizottsága az alkotmány részleges módosításáról, az egyesülési és a gyülekezési jogról szóló tervezetet is tárgyalták a képviselők - Csaknem kétezren követelik aláírásukkal dr. Vida Miklós országgyűlési képviselő visszahívását, erről tartott sajtó tájékoztatót FIDESZ - A Magyar Demokrata Fórum kispesti szervezte tegnap tag-táborozót tartott - "Arad után kitudja merre" Az erdélyi menekültekről - A Bős-Nagymarosi vízlépcsőrendszer építésével kapcsolatban tárgyalt a parlament ad hoc bizottsága